Study on the physical properties of printed parts using fresh and recycled polymer powders for additive manufacturing - Ong, Wei Jie (Nanyang Technological University, 2023)
The innovative technology of 3D printing, which is also known as additive manufacturing, has the capacity to revolutionize the manufacturing sector. Many companies are already adopting this technology worldwide to remain competitive. Industries are exploring the use of recycled materials in their additive manufacturing processes to reduce expenditure and material wastage. This study examined various Polyamide 11 and 12 powders by exposing them to non-isothermal crystallization. Properties such as crystallinity, melting points, thermal shrinkage and crystal phases were studied. Percentage crystallinity was noted to be greater at slower cooling rates and at lower maximum heating temperatures. Observed trend for peak melting temperatures which was confirmed by X-ray intensities indicates that there are at least two crystal phases during crystallization. Finally, faster cooling rates promotes the formation of γ crystals for non-isothermal crystallization. The purpose of this study, conducted in partnership with HP-NTU Digital Manufacturing Corporate Lab, was to enhance HP’s research in additive manufacturing processes and printers